Kajian Creative Thinking Matematis Dalam Inovasi Pembelajaran - I Putu Suardipa (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Critical thinking ability is required by students to solve daily problems as well as problems in the future. One of the efforts that can be done improving the quality of education that focuses mainly on the development of skills and critical thinking skills of the students. The ability of creative thinking, especially in math learning, is crucial to be maximized. In this study, you will clearly be presented with definitions of creative thinking, The experts' opinion, creative thinking traits, The factors which affect creativity, The theory of creativity, creative thinking process and reference quotations in understanding the ability of students' Creative thinking in math learning.